2011
DOI: 10.1189/jlb.1010557
|View full text |Cite
|
Sign up to set email alerts
|

Rat resident testicular macrophages have an alternatively activated phenotype and constitutively produce interleukin-10 in vitro

Abstract: The ability of the rodent testis to tolerate graft alloantigens and spermatogenic cell autoantigens is well known. The mechanisms underlying this "immune privilege" are poorly understood, but the numerous resident TMs have been implicated. Although it has been assumed that TMs display a phenotype consistent with immune privilege, this has not been formally established. Consequently, TMs were isolated from adult rats and cultured under basal conditions and following stimulation with LPS and IFN-γ (classical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 60 publications
5
98
0
1
Order By: Relevance
“…of SeC in NOD mice partially reversed the pathology with the recovery of β cell function thanks to restoration of the systemic immune tolerance through a TGF-β/IDO-dependent mechanism that led to emergence of regulatory T cells (Tregs) [94]. Moreover, it has been demonstrated that TGF-β with IL-10 and activin-A, released by SeC, contribute to modulate the immune cell response in the testis, stimulating immune cells involved in the tolerogenic response, such as M2 (anti-inflammatory) macrophages, and Th2 and Treg cells [95]. Accordingly, most macrophages located in the testis show an M2 phenotype [96].…”
Section: The Immunomodulatory Properties Of Secmentioning
confidence: 99%
“…of SeC in NOD mice partially reversed the pathology with the recovery of β cell function thanks to restoration of the systemic immune tolerance through a TGF-β/IDO-dependent mechanism that led to emergence of regulatory T cells (Tregs) [94]. Moreover, it has been demonstrated that TGF-β with IL-10 and activin-A, released by SeC, contribute to modulate the immune cell response in the testis, stimulating immune cells involved in the tolerogenic response, such as M2 (anti-inflammatory) macrophages, and Th2 and Treg cells [95]. Accordingly, most macrophages located in the testis show an M2 phenotype [96].…”
Section: The Immunomodulatory Properties Of Secmentioning
confidence: 99%
“…37 Moreover, testicular macrophages in rats are less activated in response to pathogen stimulation, and they constitutively produce anti-inflammatory cytokines. 38,39 These phenotypes support testicular immune privilege. By contrast, circulating macrophages significantly infiltrate the testis in orchitis and are detrimental to spermatogenesis.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…12,13). Recently, Winnall et al (14) reported that the immune response of TM is skewed toward an alternatively activated macrophage type similar to the M2 type in mice upon treatment with both classical (LPS and IFN-g) or alternative (IL-4) activation ligands, although still a reduced capacity for proinflammatory gene expression was observed. In support of these observations, incubation with uropathogenic Escherichia coli instead of LPS increased mRNA expression of the proinflammatory cytokines IL-6 and TNF-a; however, protein levels were not elevated (15).…”
mentioning
confidence: 99%